2021
DOI: 10.3390/clinpract11040099
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcomes in Premature Placental Calcification and the Association of a Color Doppler Study: Report from a Tertiary Care Hospital in Eastern India

Abstract: Introduction: Placental calcification, identified before the 36th week of gestational age, is known as premature placental calcification (PPC). PPC could be a clue for the poor fetal outcome. However, its association with adverse perinatal outcomes is yet to be confirmed. Objective: The primary objective was to determine and compare the perinatal outcomes in pregnancies with and without documented premature placental calcification. Methodology: The present study was a prospective cohort study performed from Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…13 Studies have found that preterm placental calcification is associated with maternal and perinatal adverse outcomes (e.g., preeclampsia, at least one abnormal Doppler index, obstetric cholestasis, placental abruption, intrauterine growth retardation, maternal intensive care unit admission, low-birth-weight infants, and low perinatal APGAR scores) oligohydramnios, perinatal mortality, hypoxia due to placental insufficiency, asphyxia, and cesarean section are also seen at increased rates in post-term pregnancies compared to term pregnancies. 1,[14][15][16] Although the etiology of post-term pregnancies is not yet fully known, it has been reported in the literature that there are many risk factors for the development of a post-term pregnancy, such as obesity, primiparity, advanced maternal age, and low education level. 17,18 In our study, the presence of grade 3 placental calcification seemed to negatively affect perinatal outcomes in women at ≥40 weeks of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…13 Studies have found that preterm placental calcification is associated with maternal and perinatal adverse outcomes (e.g., preeclampsia, at least one abnormal Doppler index, obstetric cholestasis, placental abruption, intrauterine growth retardation, maternal intensive care unit admission, low-birth-weight infants, and low perinatal APGAR scores) oligohydramnios, perinatal mortality, hypoxia due to placental insufficiency, asphyxia, and cesarean section are also seen at increased rates in post-term pregnancies compared to term pregnancies. 1,[14][15][16] Although the etiology of post-term pregnancies is not yet fully known, it has been reported in the literature that there are many risk factors for the development of a post-term pregnancy, such as obesity, primiparity, advanced maternal age, and low education level. 17,18 In our study, the presence of grade 3 placental calcification seemed to negatively affect perinatal outcomes in women at ≥40 weeks of pregnancy.…”
Section: Discussionmentioning
confidence: 99%